Experimental Metaphysics - Rose, David (Advances in Experimental Philosophy, 2017)
Metaphysics, almost entirely neglected by experimental philosophers, is the central focus of Experimental Metaphysics. The volume brings together a range of views aimed at addressing the question of how cognitive science might be relevant to metaphysics. With contributions from cognitive scientists and philosophers, chapters focus on theoretical and empirical issues involving the potential role of cognitive science in metaphysics. Alongside topics such as free will, objects and causation, in which relevant empirical evidence is discussed and connected to relevant metaphysical issues, more programmatic papers explore theoretical issues centered on the connection between cognitive science and metaphysics. This balanced approach exposes metaphysicians to philosophically relevant work in cognitive science, while showing cognitive scientists the ways in which their work might be important for philosophers. Presenting cutting-edge empirical and theoretical research, Experimental Metaphysics pushes forward the discussion and encourages further engagement with issues at the intersection of cognitive science and metaphysics.